2022
DOI: 10.3389/fmicb.2022.935072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of redox and salinity-tolerant alkaline protease from Bacillus halotolerans strain DS5

Abstract: Bacillus halotolerans DS5 was isolated and identified as a halophilic microbe according to 16S rRNA analysis and the physical and chemical indices of the strain. A new alkaline protease (designated as prot DS5) from Bacillus halotolerans DS5 was produced, purified, and characterized. After 12 h incubation in the medium with 1% dextrin, 0.5% NaCl, 2% soluble starch, and 1% yeast extract (pH 7.0), it could reach the maximum enzyme activity (279.74 U/ml). The prot DS5 was stable in the pH range of 6.0–12.0 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Yousef et al 59 recovered B. halotolerans from saline mud samples and demonstrated potential cellulase production. Wen et al 60 reported that B. halotolerans produced extracellular alkaline proteases, the activity of which was the highest after 12 h of incubation.…”
Section: Molecular Identification Of Bacterial Isolatesmentioning
confidence: 99%
“…Yousef et al 59 recovered B. halotolerans from saline mud samples and demonstrated potential cellulase production. Wen et al 60 reported that B. halotolerans produced extracellular alkaline proteases, the activity of which was the highest after 12 h of incubation.…”
Section: Molecular Identification Of Bacterial Isolatesmentioning
confidence: 99%